EVALUASI TINGKAT PENGETAHUAN SWAMEDIKASI OBAT TRADISIONAL MAHASISWA PRODI KESEHATAN DAN MAHASISWA PRODI NON-KESEHATAN DI UNIVERSITAS IMELDA MEDAN - Samgryce Siagian, Hartika; Pradana, Desi (Universitas Imelda Medan, 2022)
The choice of self-medication is used as an excuse by the public to break the chain of the spread of Covid-19, but if it is not done properly it can pose a risk to health. Self-medication will be successful if the community knows adequate information such as recognizing the symptoms of the disease, choosing generic or traditional medicine products according to indications, following the instructions for use and monitoring the results. Knowledge about self-medication is one of the objects related to health that is obtained from the results of one's own experience. The selection and use of medicines (including herbal and traditional products) in an effort to treat a disease or self-identifiable symptom is called self-medication. Based on the results of the study, it shows that the field of study that students take affects the level of knowledge about logos on traditional medicine packaging. Students with Health study program have high knowledge of 100% compared to students with non-health study programs who have high knowledge of 53.3% about traditional medicine. This is because students in the health sector better understand and learn things related to health sciences, including information about traditional medicine self-medication. The average percentage obtained from research data on the level of knowledge of traditional medicine self-medication in students in the Health and non-health fields at the University of Imelda Medan is 76.9% (high category), this is different from research conducted by Cristiana (2014) on knowledge about traditional medicine among students at Sanata Dharma University Yogyakarta whose results are in the high category (75.1%). This can be influenced by the environment and the availability of facilities as a source of correct and appropriate information about traditional medicine self-medication. A person's knowledge is also influenced by what is obtained through the eyes and ears of the individual itself which is the main factor in the formation of an attitude or action.